2009
DOI: 10.1111/j.1865-1682.2008.01063.x
|View full text |Cite
|
Sign up to set email alerts
|

Bluetongue in Belgium: Episode II

Abstract: Bluetongue (BT) is an arthropod-borne viral disease of ruminants. In August 2006, domestic ruminant populations in Northern Europe became infected with BT virus serotype 8 (BTV-8). The first BTV-8-case of the year 2007 in Belgium was notified in July. This case was the starting point of a second wave of BT outbreaks. The main objective of this study was to describe the evolution and the clinical impact of the second episode of BT in Belgium. In addition, the main differences with the previous episode (August-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 12 publications
0
18
1
1
Order By: Relevance
“…BTV-8 NET2006 is considered to be a highly pathogenic virus (both in terms of morbidity and mortality) and the cause of one of the largest outbreaks of bluetongue in history (4851). However, in our experimental setting, we did not find any difference in virulence between BTV-8 NET2006 and another serotype, such as BTV-2 IT2000 , which was isolated in Italy in the year 2000 from a naturally occurring case of bluetongue in sheep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BTV-8 NET2006 is considered to be a highly pathogenic virus (both in terms of morbidity and mortality) and the cause of one of the largest outbreaks of bluetongue in history (4851). However, in our experimental setting, we did not find any difference in virulence between BTV-8 NET2006 and another serotype, such as BTV-2 IT2000 , which was isolated in Italy in the year 2000 from a naturally occurring case of bluetongue in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the North European BTV-8 strains that spread since 2006 in Northern Europe is considered highly virulent, as it induced high levels of mortality in naive sheep and in some cases also caused severe clinical disease in cattle (4851). On the other hand, it is interesting to note that no clinical cases of disease were observed even in sheep when BTV-8 reached Northern Italy and Sardinia a few years later (G. Savini, personal communication).…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that the winter season of 2006/2007 would halt the BTV epidemic, assuming that the chain of transmission would be broken by a stop in the life cycle of the vector because of low temperatures. However, during 2007 it became evident that BTV-8 had survived the winter in Western Europe and a re-emerging epidemic quickly developed within the originally affected countries, affecting approximately 40 000 locations with ruminants [5-7]. In addition, BTV-8 was introduced into the United Kingdom, Denmark, Switzerland and the Czech Republic.…”
Section: Introductionmentioning
confidence: 99%
“…This has resulted in increased research activities in virus transmission, on detailed reporting of these outbreaks [24], [25] and in initiation of modelling studies, for example [26][28].…”
Section: Introductionmentioning
confidence: 99%